Analisis Kinerja Perbankan Syariah 2018-2022 Dengan Menggunakan Pendekatan Islamicity Performance Index - Solatiah Nasution; Pani Akhiruddin Siregar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to analyze the financial performance of Indonesian Sharia Peranakans for the 2018-2022 period using the Islamicity Performance Index approach. CAR, BOPO, and NPF are the financial ratios which are the variables that will be examined, and the Profit Sharing Ratio is the financial ratio of the Islamicity Performance Index which will be analyzed for its performance. The formulation of this research is: How is the Performance of Indonesian Sharia Banking for the 2018-2022 period using the Islamicity Performance Index Approach? and whether there is an influence of CAR, BOPO, and NPF financial ratios on the Profit Sharing Ratio. This study uses a quantitative research method with secondary data in the form of financial reports obtained from the Sharia Banking Statistics of the Financial Services Authority (SPS OJK). The results of the research analysis that has been carried out, it can be seen that the financial ratios of CAR, BOPO, and NPF affect the Profit Sharing Ratio, where this profit sharing ratio is one of the main objectives of Indonesian Islamic Banking. The recommendation for this researcher is that it is better for Indonesian Islamic Banking to further increase the PSR ratio or profit sharing so that it is important to identify the extent to which a bank has achieved its goals, because the large acquisition of profit sharing for Islamic banks will later become an advantage for the bank itself.